Perbandingan efektivitas permen karet yang mengandung ekstrak teh hijau â€œcamellia sinesisâ€ dengan permen karet yang mengandung xylitol terhadap penurunan tingkat halitosis pada mahasiswa di Universitas Udayana - I Dewa Md Bagus Putra Baskara; Desak Nyoman Ari Susanti; Ratna Kusumadewi Giri (Bali Dental Journal, 2019)
Introduction: Halitosis is a oral maloudour that comes from mouth and caused by Volatile Sulfure Compounds. The Solution to overcome the malodour is by chewing gum. Chewing gum that often consumed by a lot people is chewing gum that contain green tea extract and chewing gum that contain xylitol. The purpose in this study is to compare the efectiveness of chewing gum that contain green tea extract and chewing gum that contain xylitol in reduce halitosis rate on Udayana University student. Method: This study used an experimental study, with 32 student on Udayana University as a sample that divided into 2 groups including groups of study subject that were instructed to chew gum that contain green tea extract and groups of study subject that were instructed to chew gum that contain xylitol. The sample was taken by using purposive sampling technique. Result: The result in this study show chewing gum contain green extract is more effective in reducing halitosis based on the halitosis level measurement that show constant value at minute 20 to minute 40 with mean 2,13 compared with chewing gum contain xylitol that have 2,88 value. There are significant differences on the effectiveness of chewing gum contain green tea extract and chewing gum contain xylitol to reduce the halitosis level with the p value 0,000 (p<0,05). Conclusion: Chewing gum containg green tea extract is more effective to reduce halitosis compared to xylitol chewing gum.